The Anaesthesiologist and Palliative Care in a Newborn with the Adam “Sequence” - Alberto Vieira Pantoja; Maria Emília Gonçalves Estevez; Bruno Lima Pessoa; Fernando de Paiva Araújo; Bruno Mendonça Barcellos; Ciro Augusto Floriani; Marco Antonio Cardoso de Resende (Case Reports in Anesthesiology)
Reports focusing on biomedical principlism and the role of anaesthesiologists in palliative care are rare. We present the case of a newborn with multiple craniofacial anomalies and a diagnosis of ADAM “sequence,” in which surgical removal of placental adhesions to the dura mater and the correction of meningocele was not indicated due to the very short life expectancy. After 48 hours, the odor from the placenta indicted a necrotic process, which prevented the parents from being close to the child and increased his isolation. Urgent surgery was performed, after which the newborn was transported to the ICU and intubated under controlled mechanical ventilation. The patient died a week later. The principles of beneficence, nonmaleficence, justice, and respect for autonomy are simultaneously an inspiratory and regulatory framework for clinical practice. Although only necessary procedures are defended, which suggests a position contrary to invasive interventions at the end of life, sometimes they are the best palliative measures that can be taken in cases like the one described here.